2008
DOI: 10.1021/es071718i
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Emissions from Vehicles Fueled with Diesel or Compressed Natural Gas

Abstract: A comprehensive comparison of emissions from vehicles fueled with diesel or compressed natural gas (CNG) was developed from 25 reports on transit buses, school buses, refuse trucks, and passenger cars. Emissions for most compounds were highest for untreated exhaust emissions and lowest for treated exhaust CNG buses without after-treatment had the highest emissions of carbon monoxide, hydrocarbons, nonmethane hydrocarbons (NMHC), volatile organic compounds (VOCs; e.g., benzene, butadiene, ethylene, etc.), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 26 publications
7
75
1
1
Order By: Relevance
“…Hesterberg et al 1 previously reported the highest emissions of total 2-, 3-, and !4-ring PAH compounds in diesel transit and school buses lacking aftertreatment. With use of aftertreatment, Hesterberg et al 1 reported that PAH emissions for transit buses were significantly reduced (on average 60-97% reductions, depending on the aftertreatment type and the number of PAH rings) and of a similar magnitude, and sometimes lower, than buses operating with compressed natural gas (CNG) fuel with and without aftertreatment. Several recent studies have characterized emissions of a suite of individual PAH species in NTDE, including those suspected to be carcinogenic.…”
Section: Pahs and Other Organic Speciesmentioning
confidence: 91%
See 3 more Smart Citations
“…Hesterberg et al 1 previously reported the highest emissions of total 2-, 3-, and !4-ring PAH compounds in diesel transit and school buses lacking aftertreatment. With use of aftertreatment, Hesterberg et al 1 reported that PAH emissions for transit buses were significantly reduced (on average 60-97% reductions, depending on the aftertreatment type and the number of PAH rings) and of a similar magnitude, and sometimes lower, than buses operating with compressed natural gas (CNG) fuel with and without aftertreatment. Several recent studies have characterized emissions of a suite of individual PAH species in NTDE, including those suspected to be carcinogenic.…”
Section: Pahs and Other Organic Speciesmentioning
confidence: 91%
“…1,14,17,19,25,26 For example, for the recent CARB-USC testing of four heavy-duty and medium-duty diesel vehicles operated using six different aftertreatment configurations (Table 1) and multiple test cycles, Biswas et al 17 reported consistent PM mass reductions of >90%, observing in all cases PM emission rates of less than 0.01 g/mile (Figure 2). Given the role of chemical composition as a key factor affecting DEP toxicity, recent studies have further investigated how emissions of specific DEP constituents are impacted by the use of different aftertreatment technologies.…”
Section: Changed Chemical Composition Of Dep In Ntdementioning
confidence: 97%
See 2 more Smart Citations
“…Taken together, measurement of urine 3-HPMA may represent a novel theranostic approach for SCI. Since acrolein may potentially be linked to many other conditions, such as cancer, 2,[25][26][27][28] aging, 29 pollution, 30,31 and smoking, 32,33 the benefits of this study has the potential to significantly enhance human health.…”
Section: Figmentioning
confidence: 99%